Contribution of human papilloma virus to the incidence of squamous cell carcinoma of the head and neck in a European population with high smoking prevalence. Issue 4 (March 2015) - Tinhofer, I.; Jöhrens, K.; Keilholz, U.; Kaufmann, A.; Lehmann, A.; Weichert, W.; Stenzinger, A.; Stromberger, C.; Klinghammer, K.; Becker, E.-T.; Dommerich, S.; Stölzel, K.; et al.
Abstract Background Increases in incidence of oropharyngeal squamous cell carcinoma (OPSCC) in countries with falling tobacco use have been attributed to a growing role of human papilloma virus (HPV) in the carcinogenesis. Trends of HPV prevalence in populations with persistently high portions of smokers are poorly characterised. Patients and methods Registry data from East Germany were used to determine incidence trends between 1998 and 2011. Data from patients treated at the Charité University Medicine Berlin between 2004 and 2013 (cohort 1, N = 436) were used for estimation of trends in HPV prevalence, smoking and survival. HPV prevalence was prospectively confirmed in cohort 2 (N = 213) comprising all primary HNSCC cases at the Charité in 2013. Results Between 1998 and 2011 incidence of both OPSCC and non-OPSCC increased. An increase in HPV prevalence (% of HPV+ cases in 2004–2006 versus 2012–2013: 27% versus 59%, P = 0.0004) accompanied by a moderate decrease in the portion of current smokers was observed in OPSCC but not in non-OPSCC. The change in disease epidemiology in OPSCC was associated with significant improvement in overall survival. Increased HPV prevalence in OPSCC (48%) compared to non-OPSCC (11%) was confirmed in cohort 2. Conclusions Despite clear differences to the United States in terms of tobacco use, the increase in OPSCC incidence in a European population was also mainly attributed to HPV, and the HPV status significantly affected prognosis. For clinical trial design it is important to consider the large group of smokers within HPV-induced OPSCC.